Retrograde study of patients with adenomyosis at tertiary health centre, a spectrum from clinical presentation to its final diagnosis and treatment - Patel, Hemali; Kanani, Kishankumar; Bhankhar, Ronak; Dhameliya, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Adenomyosis is a disease where ectopic endometrial glands affect the muscular wall of the uterus. It is considered a specific entity in the PALM-COEIN FIGO (polyp; adenomyosis; leiomyoma; malignancy and hyperplasia; coagulopathy; ovulatory dysfunction; endometrial; iatrogenic; and not yet classified- International Federation of Gynaecology and Obstetrics). Aims and objectives were to diagnose adenomyosis accurately with help of data of clinical findings and imaging modalities. Methods: It was a retrospective study done at tertiary hospital, Junagadh from June 2022 to November 2022. The HPE reports and case records of all the hysterectomy specimen were reviewed. Data regarding age, parity, symptoms, obstetric history, examinations, co-morbidities, investigation findings and treatment modalities were noted. They were tabulated and analysed. Results: Out of the 50 patients, 30 patients (60%) were in the age group of 41-50 years. The prevalence of adenomyosis in our study was only 6% in post-menopausal women when compared to the age group 41-50 years (60%). Multiparous women had 92% incidence of adenomyosis. 62% had menstrual disturbances. Dysmenorrhea and dyspareunia were the next common symptoms. Fibroid was the commonest associated pathology 44%. 32% had endometrial hyperplasia, whereas 68% had no pathology. Imaging picked up only 36% of cases contrary to 28% of clinical diagnosis and was raised to 64% with gross examination of specimen and 100% with HPE. Conclusions: Better modality to diagnose adenomyosis is clinical presentation. USG failed to diagnose all the cases. Gold standard modality is histopathological examination.